The Authority of the Public Administration to Protect Morality in the Family and Society - Hussein, Dr. Mustafa Rasool; Saeed, Dr. Zana Rafiq; Sharif, Rezan Saeed Hama (Journal of Legal and Political Studies, 2018)
The authority of the public administration to protect morality in the family and society The concept of public morality is not the same in all societies; it is developed and changed by changing place and time and the rules of which are a major part of it. The administration must strike a balance between the freedom of individuals and their authority to intervene in order to protect the public morality of the family and society. The public morality of society is a major element of the public order which falls on the state in general and the administration, in particular, the duty to protect it against the risks that they face and its duty does not need an article to be decided and if found this article, its role would be limited only to emphasize the duty of the state which reflects in protecting the principles of the family or society and its ethics, as this is part of the guarantee of the existence of the state and its continuity and preservation of its identity.
Keywords: public administration; public morality; freedom of individuals; public order